Parenting dalam Surah Luqman Ayat 11-19 (Kajian Historis Keluarga Luqman al-Hakim) - Salwa Nabila; Ahmad Nabil Amir (IAT dan ILHA, UIN KH ABDURRAHMAN WAHID, 2022)
The background of this research is the lack of attention of parents towards their children because parents are too busy with their activities then children feel less affection. This study aims to find out how the historical side of the concept of parenting in surah Luqman verses 12-19 and its contextualization in the present. This article is a type of qualitative research with a library research approach using Fazlur Rahman's double movement theory. The subject of this research is parenting verses in surah luqman verses 12-19. Data will be collected using documentation techniques and data will be analyzed using a systematic-literature review. Based on research conducted by processing various existing data, two results have been obtained, first, from a historical perspective in surah Luqman verses 12-19, it contains 8 points of wisdom, parents teach their children to be grateful, children have a monotheistic spirit, chidren do birrul walidain to parents, all children’s actions will be rewarded, children must be discipline in praying, children don’t be arrogant, children may be good in behavior and polite, and children must be honest and open. Second, contextualization in parenting which produces 8 points consists of two forms, both are the form of spiritual parenting and the form of social parenting.